Konsep Dasar Kepemimpinan : Dari Definisi Hingga Tipologi Pemimpin Efektif - Rizal Andreansyah; M. Imamul Muttaqien (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Leadership is a critical aspect of organizational management, influencing individual and group behavior to achieve shared goals. This article explores the foundational concepts of leadership, encompassing definitions, theories, and typologies of effective leaders. The study employs a literature review method, drawing on recent academic journals, proceedings, and books. Findings emphasize that effective leadership involves adaptive strategies tailored to organizational needs and the dynamic challenges of the modern era. Key leadership typologies, including transformational, transactional, and situational leadership, are highlighted as crucial for fostering innovation and organizational growth. The study underscores the need for leaders to balance vision, influence, and motivation to achieve sustainable success.